2005
DOI: 10.1097/01.fpc.0000173485.59430.49
|View full text |Cite
|
Sign up to set email alerts
|

Association of N-acetyl transferase 2 gene polymorphism and slow acetylator phenotype with young onset and late onset Parkinson's disease among Indians

Abstract: Specific SNPs and SNP haplotypes in NAT2 and slow acetylator phenotype are significantly associated with YOPD and to a lesser extent with LOPD among Indians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Only a few studies focused on patients with early-onset PD [43,49,53,54,58]. Among these, only three [43,54,58] provided sufficient information to analyze the putative effect of the NAT2 acetylation status (inferred phenotype based on NAT2 genotypes) in the risk of developing PD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only a few studies focused on patients with early-onset PD [43,49,53,54,58]. Among these, only three [43,54,58] provided sufficient information to analyze the putative effect of the NAT2 acetylation status (inferred phenotype based on NAT2 genotypes) in the risk of developing PD.…”
Section: Resultsmentioning
confidence: 99%
“…Five of the 13 studies in which NAT2 phenotypes could be classified as rapid or slow acetylators showed a significantly increased risk of developing PD in slow acetylator individuals [32,47,[49][50][51], while the other eight reported lack of association [43,44,46,48,54,58,61,63]. Although the crude odds ratio (OR) for the whole series was not significant, the diagnostic OR (1.35; 95% CI = 1.01-1.81) was consistent with a modest association between slow acetylator phenotypes and the risk of developing PD (Figure 1(a)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lung cancer and smoking NQO1 0.048 (Rosvold et al, 1995) Induced CYP1A2 metabolic activity CYP1A2 <0.05 (Nakajima et al, 1999) Risk of colorectal cancer SULT1A1 0.009 (Bamber et al, 2001) Myocardial infarction GCLM <0.001 Ethnic differences in risk of heart failure ADRA2C, ADRB1 <0.001, 0.004 (Small et al, 2002) Successful weight reduction by sibutramine GNB3 0.031, 0.004 (Hauner et al, 2003) Vulnerability to illegal drug abuse HTR2B 0.0335 (Lin et al, 2004) Caffeine metabolism CYP1A2 0.036, 0.038 (Chen et al, 2005) Risk of young onset, late onset Parkinson disease NAT2 0.003 (Chaudhary et al, 2005) Coffee intake and risk of myocardial infarction CYP1A2 0.04 (Cornelis et al, 2006) Smoking and obesity in prostate, lung, colorectal and ovarian cancer patients DRD2 0.02, 0.007 (Morton et al, 2006) Antidepressant efficacy in depression patients GNB3 0.02, 0.03 (Wilkie et al, 2007) Risk of aspirin-intolerant asthma PTGER2, PTGER3, PTGIR, TBXA2R 0.023, 0.038 Gefitinib responsiveness in non-small-cell lung cancer EGFR 0.014, 0.029 Risk of atherosclerosis CYP2J2 0.036 Risk of toxic liver injury ABCC2 0.04 (Choi et al, 2007) Risk of primary lung cancer ERCC1 0.034 Induction of extrapyramidal symptoms by antipsychotics RGS2 0.003, 0.009 (Greenbaum et al, 2007) Fracture risk (bone mass) after estrogen treatment P2RX7 <0.01, 0.02 (Ohlendorff et al, 2007) Glatiramer acetate therapy for multiple sclerosis TRB@ locus 0.049 (Grossman et al, 2007) (Bertina et al, 1994) Risk of type-2 diabetes PPARG 0.002 (Altshuler et al, 2000) Risk of Crohn disease NOD2 2×10 Partial list (limited to two dozen examples) of recent GWA studies in which one or a few SNPs are associated with a complex disease or multiplex phenotype (note highly significant P-values of <1 × 1(10 −6 ).…”
Section: Abbreviationsmentioning
confidence: 99%